2017
DOI: 10.1634/theoncologist.2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase ε Deficiency Leading to an Ultramutator Phenotype: A Novel Clinically Relevant Entity

Abstract: Two cases of metastatic colorectal cancer with a POLE mutation, both of which were ultramutated and microsatellite stable, are presented and discussed from the standpoint of the basic biochemical mechanisms leading to a unique phenotype in POLE deficiency, the challenges faced with interpreting the genomic profiling of tumors in this important subset of patients, and the potential clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…32,33 Previous studies have also found that hypermutated MSS tumors harbored POLE mutations. 34,35 Four cases with hypermutated MSS tumors harboring POLE mutations were also observed in the present study. In a population-based cohort study on MSS CRC, POLE mutations were associated with lower risk of recurrence.…”
Section: Discussionsupporting
confidence: 72%
“…32,33 Previous studies have also found that hypermutated MSS tumors harbored POLE mutations. 34,35 Four cases with hypermutated MSS tumors harboring POLE mutations were also observed in the present study. In a population-based cohort study on MSS CRC, POLE mutations were associated with lower risk of recurrence.…”
Section: Discussionsupporting
confidence: 72%
“…In support of this, we observed a trend of higher somatic mutation burden in OC patients with germline ANKRD11 and POLE ‐mutations. This finding is consistent with what has been observed in endometrial and colorectal tumors with somatic POLE ‐mutations . In addition, it might also raise the beneficial potential of including POLE in gene panel testing of OC patients and their family members in order to optimize the prevention strategies to decrease their risk of OC and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is consistent with recent findings that POLE mutations can contribute to susceptibility to a broad cancer spectrum including OC. 34,35 Furthermore, it has also been reported that POLEmutant endometrial and colorectal tumors had a high somatic mutation burden, elevated expression of immune checkpoint genes and increased lymphocytic infiltration, [36][37][38][39][40][41][42][43] and therefore immune checkpoint inhibitors was recommended for treating cancers with POLE-mutations. 41,44 Similar recommendation was also demonstrated in mismatch repair (MMR) deficient cancers regardless of the cancers' tissue of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POLE ‐mutant microsatellite stable (MSS) and MSI‐H endometrial adenocarcinomas have been linked with increased immunogenic mutations . Both POLE ‐mutant and MSI‐H endometrial cancers demonstrate enhanced antitumor immune activity with infiltration of T lymphocytes . The histologic appearance of the endometrial tumor is not a reliable predictor of the underlying molecular defect, especially for the POLE ‐mutant subgroup, which has been previously reported to show low‐grade or high‐grade endometrioid, serous, or mixed histology.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%